I-UPQC para melhoria da qualidade da energia elétrica em aerogeradores de velocidade fixa - Uchôa, Juliana Izabel Lara (2015)
Fixed speed wind turbines completely dominated the market until the mid-1990s and currently. Although most installed wind turbine are variable speed, many fixed speed wind are still in operation. In this context, this work presents a study concerned to coordinated operation of FACTS (Flexible Alternating Current Transmission Systems) device with fixed speed wind energy conversion system (WECS) equipped with a squirrel cage induction generator. The applied FACTS device is based on the control strategy of the Unified Conditioner Power Quality with inverted topology (i-UPQC), and consists of two static converters connected in back-to-back topology. A model was developed in the software PSCAD/EMTDC, tested under four different scenarios and discussed in order to validate the presented theory. The i-UPQC performance was analyzed for improving voltage quality in the point of common coupling (PCC), reduction of the harmonic currents drained from the wind turbine, and increasing the induction generator capacity to remain connected during a momentary collapse in the grid voltage. The i-UPQC presented good performance due to its capability to warrant the quality in the PCC voltage in spite of the wind variation and that the voltage sags at the PCC do not change the stator voltages. About the generator current, the i-UPQC has kept the stator current free of harmonic components and the effect of unbalanced loads. Under normal operation it was demonstrated that one of the I-UPQC converters can be sized as 50% of the generator rated power, which is an advantage for real implementation. A comparison between two ways to connect the I-UPQC to the grid, along with the wind turbine, was made. The series converter connected between the wind turbine and the parallel converter, or between parallel converter and the common connection point (PCC). It was concluded that the shunt converter connected to the generator presents better performance than the series converter due to series converter currents are less than the stator currents. Under this configuration, there is no active power current from the generator injected in the PCC during voltage sags.